Analysis of Receivable Customer Management at the Republic of Indonesia Civil Servants CooperativeThe work of Bhakti Palu - Guasmin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This research is to examine and analyze the effectiveness of managing and controlling customer Receivables at the Karya Bhakti Palu Indonesian Republic Employee Cooperative for the 2014-2018 period, using arrears ratios and collection ratios, accounts receivable turnover ratios, and the average age of accounts receivable to overcome bad debts and to increase the financial effectiveness of cooperatives, the arrears ratio in 2014 – 2018 KPRI Karya Bhakti Palu can minimize the number of outstanding receivables. This can be proven by the value of the arrears ratio from 2014-2018. There were <50% of the outstanding receivables from the total outstanding receivables in the same period. Judging from the billing ratio, in 2014, it was 92%. In 2015 it was 89%. In 2016 it was 86%. In 2017, it was 88%. In 2018 it was 91%. KPRI Karya Bhakti Palu has a pretty good collection achievement because it has a percentage from 2014-2018, almost reaching 100%. Even though in 2017, there was a decline in billing value. However, it still achieves a pretty good percentage value when viewed from the effectiveness criteria for the collection ratio, which is > 50% of the total receivables outstanding in the same period. Receivables turnover ratio from this ratio during 2014-2018 Koperasi Pegawai Republik Indonesia Karya Bhakti Palu has a pretty good RTO value. This can be seen from the smaller percentage of accounts receivable turnover. Because the effectiveness criterion for the receivables turnover ratio is that the greater the average receivables, the better the performance of the cooperative, whereas if the average receivables are equal to zero (0), it means that the joint no longer has receivables, or in other words, all receivables have been collected, through several ratios, namely, the arrears ratio, billing ratio, accounts receivable turnover ratio and control of receivables is running effectively.